MORPHOMETRIC ANALYSIS OF Coptotermes sp. POPULATION FROM TWO DIFFERENT NESTS - Astuti Arif; Ira Taskirawati; . Affandi (PERENNIAL, 2010)
The aim of this research is to study morphmetric variation of external anatomy of subterranean termite (Coptotermes sp.). The samples were collected from two different nests, i.e. Laboratory of Forest Product Engineering and Diversification, Hasanuddin University (site A) and Kompleks Perumahan Dosen Unhas, Tamalanrea (site B). Resulted data were statistically analyzed for mean, standard deviation, standard error and coefficient of variability. The mean values of the different population samples were compared by using student‘t’ test according to SPSS Ver.12. For each individual soldier and worker, 54 variables of external characters were measured. The result showed that some external characters of soldier and worker casts were significantly different with different locations. In soldier casts, eleven of 54 variables were found to be significant different in length and width of caput, length and width metathorax, mesothorax length, length and width of abdomens, scape length, flagellum width, femur width, and width tibia. Whilst, in worker casts, 11 of 54 variables were found to be significant different in mesothorax length, scape length, flagellum width, trochanter width, tibia length, tarsus length, and claw width. However, morph metric of external characters of Coptotermes sp. at two locations was generally relative same in terms of coefficient of variability. Key words: Morphometric analysis, Coptotermes sp.